1999
DOI: 10.2337/diacare.22.2.280
|View full text |Cite
|
Sign up to set email alerts
|

alpha-Lipoic acid treatment decreases serum lactate and pyruvate concentrations and improves glucose effectiveness in lean and obese patients with type 2 diabetes.

Abstract: Treatment of lean and obese diabetic patients with LA prevents hyperglycemia-induced increments of serum lactate and pyruvate levels and increases SG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
94
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(100 citation statements)
references
References 0 publications
6
94
0
Order By: Relevance
“…In 3T3-L1 adipocytes, similar results were reported with respect to the ability of LA to protect against the H 2 O 2 -induced loss of insulin-stimulated glucose uptake (21). Because therapeutic concentrations of LA fall within this micromolar range (17,18,22), it is possible that the protective effect of LA on insulin action in vitro is linked to its therapeutic effect in vivo.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In 3T3-L1 adipocytes, similar results were reported with respect to the ability of LA to protect against the H 2 O 2 -induced loss of insulin-stimulated glucose uptake (21). Because therapeutic concentrations of LA fall within this micromolar range (17,18,22), it is possible that the protective effect of LA on insulin action in vitro is linked to its therapeutic effect in vivo.…”
Section: Discussionsupporting
confidence: 66%
“…More recently, it has been observed that chronic oral administration of LA exerts a small but significant effect on insulin sensitivity in patients with type 2 diabetes (17,18). Because the major action of insulin in vivo is to enhance glucose disposal via skeletal muscle glucose transport, it is likely that skeletal muscle is a primary target for LA action.…”
mentioning
confidence: 99%
“…15,16 Exogenous treatment with R-ALA has also been shown previously to improve insulin-stimulated whole body and skeletal muscle glucose disposal in the insulin-resistant obese Zucker rat 15,[17][18][19] and treatment with a racemic mixture of ALA enhances whole-body glucose disposal in investigations of type 2 diabetic human subjects. [20][21][22][23] Because evidence to date indicates that the effects of CLA and R-ALA are mediated through different cellular mechanisms (the former through activation of PPARs and the latter via a reduction in oxidative stress), it was hypothesized that when CLA and R-ALA are used in combination, there would be at least an additive interaction in improving insulin-stimulated glucose transport in skeletal muscle of insulin resistant animals and humans. In this context, the purpose of the present investigation was to assess the interactions of CLA and R-ALA (at low, individually minimally effective doses, and at high, individually maximally effective doses) on whole-body glucose tolerance and insulin-stimulated glucose transport in skeletal muscle in an animal model of insulin resistance-the female obese Zucker rat.…”
mentioning
confidence: 99%
“…In recent years, evidence has accumulated suggesting that α-LA has a wide range of benefits in the treatment of diabetes. Bitar et al [5] demonstrated that α-LA could partly ameliorate insulin resistance in type 2 diabetic rats, while others had reported additional antidiabetic effects in earlier rodent [4,6], and human studies [7]. In vitro approaches have also shown that α-LA can enhance glucose disposal in skeletal muscle [8] and adipocytes [9], and suppress hepatic gluconeogen-esis [10].…”
mentioning
confidence: 99%